THE PENGARUH VIDEO PEMBELAJARAN UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS II SD NEGERI 104235 NAGA TIMBUL: peserta didik - Junisyah Nur Armayani; Dara Fitrah Dwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The purpose of this study was to determine the effect of learning videos on the reading ability of class II students of SD Negeri 104235 Naga Timbul. The research design in this study is a one group design pre-test and post-test. The method in this study is included in the experimental type using a quantitative approach. In this study, a pre-test will be carried out before treatment and a post-test after treatment is given. Participants in the study of the effect of learning videos on the reading ability of class II students of SD Negeri 104235 Naga Timbul were all class II elementary school students who participated in the learning. And the place of research was conducted at SD Negeri 104235 Naga Timbul. The population in this study were all class II students of SD Negeri 104235 Naga Timbul in the 2023/2024 Academic Year, totaling 29 people, a sample of all class II students totaling 29 students. This study concludes that the use of learning videos has a significant effect on the reading ability of class II students at SD Negeri 104235 Naga Timbul. Based on the analysis of pre-test and post-test data, there was a significant increase in student learning outcomes after the implementation of learning videos. The test instrument used in this study, consisting of 20 test items, was proven to be valid. All test items had an r_count value greater than the r_table value, ensuring that the test could measure students' reading ability accurately. The pre-test and post-test data showed a normal distribution, as indicated by the Kolmogorov-Smirnov test. The significance value for both tests was greater than 0.05, indicating that the data followed a normal distribution and was suitable for further analysis. Analysis of the t-test results showed that there was a significant difference between the pre-test and post-test scores. With a T-count value of 7.26, which was much higher than the T-table at a significance level of 0.05, these results indicate that learning videos are effective in improving students' reading ability. The average gain of 22.48 indicates a substantial increase in students' reading ability after the intervention.